Staged carotid and coronary surgery for concomitant carotid and coronary artery disease - Antunes, PE (2011)
OBJECTIVE: To demonstrate that staged, consecutive, carotid endarterectomy (CEA) and coronary artery bypass grafting (CABG) are safe, perhaps preferable, alternative for the treatment of patients with severe carotid and coronary artery disease. METHODS: During an 8-year period ending December 1999, 77 (2.1%) of 3633 consecutive patients who were referred for isolated coronary surgery were found to have significant carotid disease and underwent CEA, and subsequently, CABG. The mean age was 65.2 +/- 5.9 years and 66 (85.7%) were males. The majority (84.4%) had triple vessel and 19.4% had left main disease. Carotid disease was unilateral in 71 patients (92.2%) and bilateral in six (7.8%), and 57 (74.0%) were neurologically asymptomatic. Only obstructions >70% were considered for endarterectomy. RESULTS: Eighty-three isolated CEAs were performed with direct clamping of the artery (mean 20.1 +/- 5.9 min) in all but one. There were no deaths. There were two strokes (2.4%) and three (3.6%) myocardial infarctions (MI). The mean admission time was 6.0 +/- 3.5 days. The staging interval was 32.4 days. During coronary surgery, a mean of 2.9 coronary grafts/patient was performed and all but one patient received at least one IMA graft. One patient (1.3%) died. There were two cases (2.6%) of MI and three patients (3.9%) had a stroke. Hence, the overall rates of perioperative mortality, MI and stroke were 1.3, 6.3 and 6.3%, respectively. The mean admission time was 8.3 +/- 6.0 days. CONCLUSIONS: Staging of carotid and coronary operations resulted in low global perioperative mortality and morbidity rates in these high-risk patients and is a good alternative therapeutic option.